Análise da coordenação e seletividade das proteções do sistema de 123 nós do IEEE com elevada integração de geração distribuída baseada em inversores - Cristofano Junior, Amauri Cesar (2023)
The electric power systems are responsible for supplying electrical energy from reliably, continuously and safely to consumers, ensuring quality in supply. It is essential that these systems operate correctly, even in abnormal situations such as short circuits in order to maintain these characteristics. This work aims to study the impacts of large-scale integration of Distributed generation based on inverters in a electric power system. The characteristics will be analyzed of this type of generation and its behavior during short circuits. Furthermore, they will evaluated the impacts caused by this integration in the project of protection, coordination and selectivity system. The electrical system used as an example was the IEEE 123-node model. To perform simulations, the OpenDSS software was used, which was controlled by the PyCharm software, through the Python programming language. The integration of photovoltaic generators into the electrical system was performed using OpenDSS. This software made it possible to calculate the power flow and the short-circuit currents, taking into account the presence and behavior of these generators. PyCharm, in turn, made it possible to program and control the simulations in the OpenDSS, using the Python language. With this integration, it was possible to automate and facilitate the process of simulation and analysis of the impacts of distributed generation on the system electrical studied. The use of these tools and approaches allowed to carry out accurate simulations and detailed, evaluating the behavior of the electrical system with the integration of generators photovoltaics. These analyzes are fundamental to understanding the impacts of generation distributed in the protection, coordination and selectivity project of the system, as mentioned before. It was developed in a protection project, in which intelligent electronic devices were used and fuses to realize overcurrent protection functions 50 and 51, according to the symbology adopted by the ANSI standard. Based on this project, detailed analyses, element by element, were carried out to assess whether the massive insertion of inverter-based generators would affect system coordination and selectivity electric. A concern when integrating inverter-based generators is that their short-circuit currents may change the characteristics of the electrical system, leading to a lack of coordination of protections and compromising selectivity. The analysis carried out had the objective of verifying whether this concern was valid. In the study carried out, calculations of short-circuit currents were initially made without integrating the inverter-based generators. Then, an analysis was performed considering the variation of the nominal power of the generators in different percentages: 20%, 40%, 60%, 80% and 100%. During this analysis, the objective was to verify the maximum variation of short-circuit currents results based on these variations in the nominal power of the generators. The results obtained indicated that the three-phase short-circuit currents presented a maximum variation of approximately 7.58%, while short-circuit currents single phase presented a maximum variation of about 6.73%. These results suggest that the introduction of inverter-based generators and variations in nominal power of these generators have a relatively small impact on short-circuit currents of the electrical system studied. This information is valuable for assessing the influence of inverter-based generators on short-circuit currents and provide a solid basis for sizing adequate protections, guaranteeing the reliability and security of the electrical system in short-circuit situations, even with the presence of generators based on inverters. The protections parameterized in the intelligent eletronic devices, 50 and 51, do not present undue operations nor loss of coordination and selectivity. This is due to the fact that the maximum variation found is not enough to uncoordinate the system and influence pick-up levels of the intelligent eletronic devices. Despite the massive insertion of inverter-based generators causing changes in the power flow characteristic in the studied circuit, the contributions of these generators in the short-circuit currents (ICC) can impact the operation of fuses, which are designed to operate close to Nominal chain. The parameterized protections in the intelligent eletronic devices proved to be robust and maintained coordination and selectivity, while fuse operation can be affected by the contribution of short-circuit currents of inverter-based generators. Therefore, it is important to consider these aspects when designing and dimensioning protections and safety devices in the electrical system studied.